MENENTUKAN PRODUK MAKANAN OLAHAN PRIORITAS EKSPOR INDONESIA - Umar Fakhrudin; . Hasni (Trade Analysis and Development Agency, Ministry of Trade of Republic of Indonesia, 2009)
Processed Food is classified as Indonesia Potential Export Commodity, which its export in last five years (2003-2003) was growth for 15,6% per years In the world market, Indonesian Processed food market share relatively lower (approx. 0.7 % ) than global demand growth. The share market growth of Indonesian Processed Food is only 5% per year, meanwhile the global demand growth is 12% year. This stipulation makes Indonesia has potential chance to enlarge the market in the world. Indonesia should have effective strategy of making priority of the product. The product that is prioritized is going to be treating as the export accelerator. The product was chosen must have not only good export performance but also have potential global demand and potential domestics support as well as social economics impact. The result of this research is Indonesia gets an overview of the sustainable processed food products for the future and makes them as Indonesian brand image in the global market.